MORAL-RELIGIOUS DETERMINANTS OF PROTECTION OF THE CRIMINAL LEGAL PROCEDURE PARTICIPANTS - N. T. Kereseleidze (Russian Journal of Economics and Law)
The article is dedicated to the issue of necessity to take into account the religious views and traditions while carrying out investigative actions (such as survey or body search) in relation to Muslim women, as well as the possibility of forced survey of the complainant and the witness.